Determining the factors affecting the demand for unit trust : evidence from Saham Sabah Berhad / Adam Maljan - Maljan, Adam (2014)
First and foremost, the research topic conducted by the researcher is The study on The Factors Affecting the Demand for Unit Trust: Evidence from Saham Sabah Berhad. The contents of this report consists of several parts such as: